Homeownership for the urban poor under Hu-Wen administration: issues and challenges - Tan, Teck-Hong * (2013)
Under Hu-Wen administration, the government has taken a series of housing tightening measures to rein in sky-high house prices with the focus switching to curb speculative demand for housing from the supply of new housing coming on the market. Despite efforts by the government, the price is ironically still remained high. The sharp hike in house prices in the past 10 years has made homeownership a great challenge to vulnerable groups of people, particularly the urban poor in China. The purpose of this paper is to highlight a number of issues that have undermined the success of these tightening measures. There is insufficient space within the city to house all urban inhabitants. Therefore, it is important to plan and undertake proper and well-connected housing development projects to keep up with the rapid urbanization and rising and housing infrastructure needs of urban inhabitants. To ensure there is no disparity between the state objective and the actual outcomes of the noble measure, more bold changes need to be introduced by the new leaders in the housing delivery system to stabilize house prices in China.